Hemagglutinin-esterase-fusion (HEF) protein of influenza C virus - Mingyang Wang; Michael Veit (Protein & Cell, 2015)
ABSTRACT Influenza C virus, a member of the Orthomyxoviridae family, causes flu-like disease but typically only with mild symptoms. Humans are the main reservoir of the virus, but it also infects pigs and dogs. Very recently, influenza C-like viruses were isolated from pigs and cattle that differ from classical influenza C virus and might constitute a new influenza virus genus. Influenza C virus is unique since it contains only one spike protein, the hemagglutinin-esterase-fusion glycoprotein HEF that possesses receptor binding, receptor destroying and membrane fusion activities, thus combining the functions of Hemagglutinin (HA) and Neuraminidase (NA) of influenza A and B viruses. Here we briefly review the epidemiology and pathology of the virus and the morphology of virus particles and their genome. The main focus is on the structure of the HEF protein as well as on its co- and post-translational modification, such as N-glycosylation, disulfide bond formation, S-acylation and proteolytic cleavage into HEF1 and HEF2 subunits. Finally, we describe the functions of HEF: receptor binding, esterase activity and membrane fusion.